Law Students’ Perceptions of Victims’ Rights Protection in the Implementation of Restorative Justice under Law Number 20 of 2025 on the Indonesian Criminal Procedure Code - Tries Edy Wahyono; Eka Sudibya; Hendrawan Nurcahyo (International Journal of Sustainable Law, 2026)
Restorative justice has become part of Indonesia’s criminal procedure reform through Law Number 20 of 2025 concerning the Indonesian Criminal Procedure Code. This study examined law students’ understanding of victims’ rights protection and their perceptions of the distinction between voluntary reconciliation and pressured settlement in restorative justice proceedings. Using a descriptive qualitative approach, the study involved two law students from universities in Malang selected through purposive sampling. Data were collected through interviews and analysed through data reduction, data display, thematic categorisation, and conclusion drawing. The findings showed that both participants viewed restorative justice as a process that should prioritise victim recovery, offender accountability, and the restoration of social relationships. Victims were regarded as active rights-holders entitled to information, meaningful participation, legal assistance, protection from intimidation, and material and non-material recovery. Both participants rejected the view that a signed peace agreement automatically proves voluntary consent. Voluntary reconciliation was associated with informed and freely given consent, whereas pressured settlement involved direct threats and indirect influences, including family persuasion, community expectations, economic vulnerability, institutional pressure, emotional exhaustion, and unequal social status. The study concludes that restorative justice should be assessed by whether victims are genuinely heard, protected, restored, and able to decide independently.